FOUNDATION OF VISION AND MISSION FORMULATION EARLY CHILDHOOD EDUCATION INSTITUTIONS (MULTI-SITE STUDY ON AUM PAUD IN JEMBER) - Jatmikowati, Tri Endang; Misyana, Misyana; Setiawan, Bahar Agus; Rofi, Sofyan; Kusumawati, Dahani (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: The main basis of this research is based on the importance of understanding the vision and mission of school institutions as ideals that want to be realized. Formulating the school's vision and mission certainly has a foundation of values ​​that form its spirit, so that there is harmony between the activities carried out by the school and the realization of the vision and mission that have been formulated. Purpose of the Study: This research aims to determine the basis for formulating the school's vision and mission at the early childhood education level. This research approach is qualitative, with data collection techniques using documentation. Methods: The data analysis technique uses content analysis using Nvivo 12. The research was conducted in 5 early childhood education schools. Results: The results of the research show that the formulation of vision. Mission in early childhood education schools is based on religious values ​​and general or non-religious values. Conclusion: The conclusion of the research results, explicit value content in the formulation of the school's vision and mission, namely religious and non-religious or general values.